2019
DOI: 10.4102/ojvr.v86i1.1781
|View full text |Cite
|
Sign up to set email alerts
|

Ixodid ticks (Acari: Ixodidae) collected from African savanna elephants (Loxodonta africana) and African forest elephants (Loxodonta cyclotis)

Abstract: Eight ixodid tick species were collected from 173 African savanna elephants (Loxodonta africana) in Kenya, northern Mozambique and Zimbabwe, and two species were collected from six African forest elephants (Loxodonta cyclotis) in the Republic of Congo. A new host record is reported for Amblyomma eburneum. A list of ticks collected from elephants in various African countries, and stored in the United States National Tick Collection, is supplied as well as an annotated checklist of the 27 ixodid tick species tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
1
6
0
2
Order By: Relevance
“…Meanwhile, its occurrence on camels in the southern, northern, and eastern regions not only illustrates its feeding on multiple hosts but also indicates its ability to thrive in arid and semi-arid agroecologies, where camels are raised. In certain African countries, this tick appears to infest African buffalo and elephants [ 61 , 62 ], which further confirms its non-selective feeding.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Meanwhile, its occurrence on camels in the southern, northern, and eastern regions not only illustrates its feeding on multiple hosts but also indicates its ability to thrive in arid and semi-arid agroecologies, where camels are raised. In certain African countries, this tick appears to infest African buffalo and elephants [ 61 , 62 ], which further confirms its non-selective feeding.…”
Section: Discussionmentioning
confidence: 71%
“…Although it affects a wide range of domestic animals, the highest infestation rate in goats suggests the presence of much of the goat population raised in arid and semi-arid agroecologies where this tick predominates. It has been shown that this tick circulates in almost all southern African countries and some in eastern Africa, such as Kenya and Sudan [ 58 , 61 , 63 ]. It appears that the tick inevitably infests many domestic animals and wildlife in these regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of R. decoloratus ticks was reported in South Africa [12,22,50] and in other African countries [40,51], and R. microplus abundance was reported in Brazil [5,52] and Malaysia [53]. The resistance of R. decoloratus to acaricide was observed in Adehan et al [54], Kariuki et al [55]. This tick species transmit Babesia bigemina and A. marginale to cattle, and heavy infestations can cause tick worry and anemia [56].…”
Section: Discussionmentioning
confidence: 99%
“…Cette tique évoquée dans la chantefable appartient à un ordre d'arachnides acariens, les Ixodida (famille Ixodidae). Au regard de publications scientifiques (Kariuki et al 2019)…”
Section: Un Acarien Ectoparasite Plurispécifiqueunclassified